PELATIHAN MANAJEMEN STRATEGI MUTU LAYANAN BIMBINGAN DAN KONSELING BERORENTASI PUBLIC TRUST PADA SMK DI KOTA BANJARMASIN - Jarkawi, Jarkawi; Prasetia, Muhammad Eka; Mahfuz, Mahfuz (Jurnal Berdaya Mandiri, 2019)
The involvement of guidance and counseling teachers in the school activities program has not been maximized. There has never been a quality audit of guidance and counseling services, Not yet having a standard operational procedure for guidance and counseling services. This service aims to improve the culture of quality guidance and counseling services through training in quality guidance and counseling service quality in Banjarmasin City. The target of service is the teachers of guidance and counseling at Vocational Schools in Banjarmasin City. Method of activities in the form of seminars and workshop about the strategy of quality guidance and counseling services. Achievement target; Strategic policy for the success of the school quality culture, strategic policy for the success of the quality culture. Targeted Output from Service; Seminar, e-ISSN Journal, Guidance and Counseling Quality Strategy Culture Guidebook.